2019
DOI: 10.1039/c8nr09932d
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Ta2O5 electron-selective contacts for high efficiency InP solar cells

Abstract: This work demonstrates stoichiometric Ta2O5 ultrathin layer as a novel and efficient electron-selective contact for planar InP heterojunction solar cells achieving an efficiency of 19.1% and a highest ever reported open circuit voltage of 822 mV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…[424] ) and singlecrystal III-V (see e.g. InP [425] ). In these structures, TSO thin-films deliver some critical (see e.g.…”
Section: Wide Bandgap Ferroelectric Oxide Thin-filmsmentioning
confidence: 99%
“…[424] ) and singlecrystal III-V (see e.g. InP [425] ). In these structures, TSO thin-films deliver some critical (see e.g.…”
Section: Wide Bandgap Ferroelectric Oxide Thin-filmsmentioning
confidence: 99%
“…175,176 Successful passivation of single InAs nanowires by a shell of Al2O3 has been reported. 175 It can also be noted that deposition of oxides such as Ta2O5, 177 ZnO, 178 and TiO2, 179 on top of InP thin film solar cells have been demonstrated to provide pas-Fig. 14.…”
Section: Vd Upscaling and Optimizationmentioning
confidence: 99%
“…Another interesting passivating electron contact is TaO x with device efficiencies up of 19.1% reported. [ 30,47 ] In other work it was shown that the oxygen deficiency level in TaO x can be altered by using radical‐enhanced ALD. [ 48 ] As an optimized oxygen deficiency is expected to enhance the electrical properties of TaO x , a composition‐controlled TaO x film could result in high device performance.…”
Section: Ald In Solar Cellsmentioning
confidence: 99%